“Tobacco-free nicotine” electronic cigarette perceptions and use among adolescents and adults in five New England states - Brittany A. Zulkiewicz; Jonathan P. Winickoff; Mark A. Gottlieb; Karen M. Emmons; Andy S.L. Tan (Addictive Behaviors Reports, 2024)
Introduction: More brands are using tobacco-free nicotine (TFN) in electronic cigarettes (e-cigarettes) and these products are becoming increasingly popular. The term TFN and claims about its properties can mislead consumers about the harms and addictiveness of TFN e-cigarettes, which may increase initiation of these products among non-smokers or influence current smokers’ decisions to adopt TFN e-cigarettes as a harm reduction measure. Methods: We conducted an observational, cross-sectional survey of 777 adolesc aged 13–17 and 655 current adult cigarette smokers residing in Massachusetts, Connecticut, New Hampshire, Rhode Island, or Vermont about their TFN e-cigarette awareness, use, perceptions, and susceptibility. We examined the association between prior awareness of TFN and use, perceptions, and susceptibility. Results: One-third of adolescents and adults reported being aware of TFN. TFN e-cigarette use was less common than tobacco-derived nicotine (TDN) e-cigarette use among adolescents (8.9 % vs. 30.5 %) and adults (21.1 % vs. 79.4 %). Compared to unaware adolescents, adolescents who were aware of TFN more frequently reported being more likely to use TFN compared to TDN e-cigarettes and that TFN e-cigarettes are more addictive than those containing TDN. Aware adult smokers more frequently reported that TFN e-cigarettes are more addictive than TDN e-cigarettes, TFN e-cigarettes cause some harm, TDN e-cigarettes cause little harm, and that TFN and TDN e-cigarettes are equally harmful than those who were unaware previously. Conclusion: Public health education campaigns are needed to educate consumers about the harms and addictiveness of TFN e-cigarettes.